Intelligent Multi-Agent Online Examination System - Anaekwe, Jane Chioma (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
ABSTRACT: Examinations are essential tools in an education system and are used to test the knowledge, learning capabilities, and progress of a student in a specific domain. Due to its importance in an academic system, it is therefore vital to have an examination system that is fair and efficient. The traditional paper-based examinations are known to have various constraints such as, their time consuming nature, delays in declaration of results, human errors and tedious evaluation/management of large amounts of paper which are prone to security risks and exam malpractice. Due to these limitations the paper based systems have received various criticisms about its efficiency and fairness. This thesis is aimed at solving the problem of the traditional paper-based exams by the introduction of an intelligent multi-agent online examination system. The system is a paperless exam integrated with intelligent agents. Each agent introduced in the system has specific duties that they perform and are capable of communicating with each other thereby forming an interconnected network. The duties of the agents include monitoring exams, providing various services during exams e.g. extra time requests, teacher requests, instant calculation and display of results, performance analysis, speed analysis, and suggestions to students and teachers on topics students need to improve in. Simulation exams (practice exams) are also provided to help students improve their performance and become familiar with the system. This approach provides a fair and efficient way of handling exams with reduced cost, workload, errors and risks thereby providing assistance and convenience to both teachers and students. Keywords: Multi-agent system, online examination system, efficient services. ………………………………………………………………………………………………………………………… ÖZ: Sınavlar, bir öğrencinin belli bir alandaki bilgisini, öğrenme becerilerini, ve ilerlemesini test etmeye yarayan elzem araçlardır. Akademik sistemdeki öneminden dolayı, adil ve verimli bir sınav sistemi önemlidir. Geleneksel kağıt tabanlı sınavlarda çeşitli kısıtlamalar olduğu bilinmektedir. Bunlar arasında zamanın boşa harcanması, sonuçların bildiriminde oluşan gecikmeler, insan hataları, büyük miktarda kağıdın değerlendirilmesi/idaresi’nin sıkıcı ve güvenlik yönünden riskler taşıması sayılabilir. Bu sorunlardan ötürü kağıda dayalı sistemler verimlilik ve adaletlilik yönünden eleştiriler almışlardır. Bu tezin amacı, akıllı, çok etmenli, çevrimiçi bır sınav sistemi ile geleneksel kağıt tabanlı sınvaların yol açtığı sorunlara çözüm getirmektir. Sistem akıllı etmenlerle entegre olmuş kağıtsız sınavlardan oluşur. Sistemdeki her etmenin kendine has görevleri vardır ve etmenler birbirleri ile konuşabilmeleri sayesinde bağlantılı bir ağ oluştururlar. Etmenlerin görevleri arasında sınavları gözetleme, sınav esnasında bazı hizmetler sunma (örneğin ek süre taleplerini değerlendirme), öğretmen talepleri, sonuçların anında hesaplanıp gösterilmesi, performans analizi, hız analizi, ve öğrenciler ile öğretmenleri öğrencinin gelişim göstermesi gereken konularda bilgilendirmesi vardır. Sistemde var olan deneme sınavları da öğrencilerin perrformansını arttırmaya ve sisteme aşinalık kazanmaya yardımcı olur. Bu yaklaşım sayesinde sınavların adaletli, verimli, azaltılmış maliyet, iş, hata ve risk ile yapılması mümkün hale gelmektedir. Anahtar kelimeler: Çok etmenli sistem, çevrimiçi sınav sistemi, verimli hizmetler.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2015. Supervisor: Assoc. Prof. Dr. Zeki Bayram.
Keywords: Computer Engineering; Intelligent agents (Computer software); Computational intelligence; Multi-agent system, online examination system, efficient services